Edukasi Pangan, Cemilan Aman Dan Sehat Di SMA Maitreyawira Kota Batam - Gunawan, Agung Arif; Saputra, Eryd; Nuryanto, Heri; Hermanto, Marsha Priscilla (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Education regarding the consumption of safe, healthy and quality food and snacks in the school environment is important for the government and related stakeholders, especially the generation with an age range of 15-18 years who of course have a tendency to consume junk food, whether it is snacks in the environment. school (canteen). It is important to provide education regarding the provision of safe and healthy food and snacks in the school environment, where school children have a tendency to consume unhealthy food or junk food around them which is currently widespread in the city of Batam. Therefore, there is a need for communication between related parties, including government, academics, industry and society; to achieve the goal of safe, quality and nutritious food circulating in society. The aims and messages to be conveyed in this Community Service activity include that the role of education is not only to provide intellectual education, but can also pay attention to the health of school students, including the food they consume.